2022
DOI: 10.1101/2022.03.10.483660
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Anatomical, ontogenetic, and genomic homologies guide reconstructions of the teeth-to-baleen transition in mysticete whales

Abstract: The transition in Mysticeti (Cetacea) from capture of individual prey using teeth to bulk filtering batches of small prey using baleen ranks among the most dramatic evolutionary transformations in mammalian history. We review phylogenetic work on the homology of mysticete feeding structures from anatomical, ontogenetic, and genomic perspectives. Six characters with key functional significance for filter-feeding behavior are mapped to cladograms based on 11 morphological datasets to reconstruct evolutionary c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 124 publications
0
5
0
Order By: Relevance
“…This keratinous filtering material, suspended from the palate of all extant species of crown mysticetes, is a neomorphism that evolved roughly 25 million years ago from early, toothed members of stem Mysticeti (Fordyce and Barnes, 1994;Thewissen, 1998;Thewissen and Bajpai, 2001;Thewissen et al, 2009;Uhen, 2010;Marx and Fordyce, 2015;Pyenson and Vermeij, 2016;Marx et al, 2016a, Marx et al, 2016bPyenson, 2017;Slater et al, 2017). Although fossilized baleen exists (Esperante et al, 2008;Bisconti, 2012;Gioncada et al, 2016;Collareta et al, 2017;Marx et al, 2017;Bosio et al, 2021), abundant fossil skulls and teeth of early mysticetes reveal that dentition gradually declined in tooth size and number as it was replaced by this new and highly adaptive key innovation (Fordyce, 1980;Fitzgerald, 2010;Berta et al, 2016;Marx et al, 2016a;Geisler et al, 2017;Lambert et al, 2017;Peredo et al, 2017;Hocking et al, 2017a;Fordyce and Marx, 2018;Ekdale and Demeŕe, 2021;Gatesy et al, 2022). Although baleen functions roughly analogously to filtering dentition, it is not homologous to teeth, the keratinous palatal ridges of some mammals, or any other tissue (Gatesy and O'Leary, 2001;Demeŕéet al, 2008;Fudge et al, 2009;Gatesy et al, 2013;Thewissen et al, 2017).…”
Section: Baleen As Metafilter With Structural Complexity and Variabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…This keratinous filtering material, suspended from the palate of all extant species of crown mysticetes, is a neomorphism that evolved roughly 25 million years ago from early, toothed members of stem Mysticeti (Fordyce and Barnes, 1994;Thewissen, 1998;Thewissen and Bajpai, 2001;Thewissen et al, 2009;Uhen, 2010;Marx and Fordyce, 2015;Pyenson and Vermeij, 2016;Marx et al, 2016a, Marx et al, 2016bPyenson, 2017;Slater et al, 2017). Although fossilized baleen exists (Esperante et al, 2008;Bisconti, 2012;Gioncada et al, 2016;Collareta et al, 2017;Marx et al, 2017;Bosio et al, 2021), abundant fossil skulls and teeth of early mysticetes reveal that dentition gradually declined in tooth size and number as it was replaced by this new and highly adaptive key innovation (Fordyce, 1980;Fitzgerald, 2010;Berta et al, 2016;Marx et al, 2016a;Geisler et al, 2017;Lambert et al, 2017;Peredo et al, 2017;Hocking et al, 2017a;Fordyce and Marx, 2018;Ekdale and Demeŕe, 2021;Gatesy et al, 2022). Although baleen functions roughly analogously to filtering dentition, it is not homologous to teeth, the keratinous palatal ridges of some mammals, or any other tissue (Gatesy and O'Leary, 2001;Demeŕéet al, 2008;Fudge et al, 2009;Gatesy et al, 2013;Thewissen et al, 2017).…”
Section: Baleen As Metafilter With Structural Complexity and Variabilitymentioning
confidence: 99%
“…Although this general three-way pattern of mysticete feeding is widely understood (Pivorunas, 1979;Berta et al, 2015, Berta et al, 2016, much speculation surrounds the origins of baleen from early toothed ancestors and the presumed original type of mysticete feeding (Fitzgerald, 2010;Boessenecker and Fordyce, 2015;Tsai and Fordyce, 2015;Marx et al, 2016a;Geisler et al, 2017;Gol'din and Startsev, 2017;Lambert et al, 2017;Peredo et al, 2017;Hocking et al, 2017b;Fordyce and Marx, 2018;Ekdale and Demeŕe, 2021;Gatesy et al, 2022). Notably, whether the earliest baleen use involved intermittent or continuous filtration remains unknown, despite much conjecture.…”
Section: Baleen As Metafilter With Structural Complexity and Variabilitymentioning
confidence: 99%
“…R. Soc. B 290: 20231932 cetaceans, several studies [62,63] proposed that the neurovascular anatomy of the upper teeth was co-opted for nourishing baleen. Lanzetti [14] showed that baleen rudiments develop alongside tooth germs within the alveolar canals of minke whales.…”
Section: (D) Convergent Redeployment Of Tooth Developmental Pathway F...mentioning
confidence: 99%
“…Comments on systematic attribution. NMV P218462 is referable to Kinetomenta (sensu [33]) based on the presence of an unsutured symphysis and distinct symphyseal groove; and to Chaeomysticeti based on the lack of mandibular alveoli, the presence of multiple relictual alveolar foramina with associated anterior sulci, and the relatively small height and dorsal placement of the mandibular canal.…”
Section: (A) Systematic Palaeontologymentioning
confidence: 99%